-Fe2O3 Nanoparticles as a Potential Sensor for Histamine Isolation - Gagić, Milica; Kopel, Pavel; Cernei, Natalia Vladimirovna; Zítka, Ondřej; Švec, Pavel; Jamroz, Ewelina; Adam, Vojtěch (TANGER, 2019)
Histamine, biologically active amine, is normally present in the body and it is involved in a local regulation of physiological processes. It occurs in food as a product of microbial decarboxylation of amino acid histidine, and consumption of histamine-rich food can lead to intoxication. Hence, its identification, quantification, and awareness of this foodborne toxin are important for food safety as it can serve as an indicator of food spoilage. This study presents a synthesis of various -Fe2O3 nanoparticles, which differ in surface functionalization, application of particles for histamine detection and isolation, and subsequent reaction of desorbed histamine with ninhydrin for final ion exchange chromatography quantification. The aim of this study was to develop easy to use, cost-effective, and error-free procedure for quantification of histamine.

Histamine, biologically active amine, is normally present in the body and it is involved in a local regulation of physiological processes. It occurs in food as a product of microbial decarboxylation of amino acid histidine, and consumption of histamine-rich food can lead to intoxication. Hence, its identification, quantification, and awareness of this foodborne toxin are important for food safety as it can serve as an indicator of food spoilage. This study presents a synthesis of various -Fe2O3 nanoparticles, which differ in surface functionalization, application of particles for histamine detection and isolation, and subsequent reaction of desorbed histamine with ninhydrin for final ion exchange chromatography quantification. The aim of this study was to develop easy to use, cost-effective, and error-free procedure for quantification of histamine.
-Fe2O3 Nanoparticles as a Potential Sensor for Histamine Isolation
Keywords: Histamine; nanoparticles; food safety; Histamine; nanoparticles; food safety